Wexler inequality and almost periodic solutions of differential equations with deviating argument of mixed type - Akhmet, M.U.; Tleubergenova, M.A. (Нелінійні коливання, 2004)
The paper is concerned with the existence and stability of an almost periodic solution of the system with deviating argument dx(t)/dt = A(t)x(t) + f(t, x(t), x(t − τ₁(t)), . . . , x(t − τk(t)). The Wexler inequality for the Cauchy matrix is used. Conditions for stability of the solution are given.